Preparation method and application of microfibrillated silk fiber aerogel

By performing multiple steps of disposable silk fiber processing and modification, a microfibrillated silk fiber aerogel material with high adsorption, hydrophobic and low thermal conductivity was prepared, which solved the problems of resource reuse and insufficient material performance in the prior art. , achieving low-cost and efficient adsorption and heat insulation effects.

CN119425628APending Publication Date: 2025-02-14DALIAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460686.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize waste biomass resources to prepare functional microfibrillated silk fiber aerogels with low cost, simple process, reusable, biodegradable, and high adsorption properties, superhydrophobic properties, and low thermal conductivity. Material.

Method used

By physically cutting and crushing, chemical treatment and mechanical grinding of waste silk fibers, a microfibrillated silk fiber suspension with micro-nano-grade special-shaped structure on the surface was prepared, and superhydrophobic modification was performed using silane coupling agent, followed by low temperature Aerogel materials were prepared by freezing and vacuum freeze-drying.

Benefits of technology

A microfibrillated silk fiber aerogel material with low density, high adsorption ratio, excellent hydrophobic performance and low thermal conductivity was achieved, and it had good adsorption, heat insulation and reusing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005091787630000011
    Figure HDA0005091787630000011
  • Figure HDA0005091787630000012
    Figure HDA0005091787630000012
  • Figure HDA0005091787630000013
    Figure HDA0005091787630000013
Patent Text Reader

Abstract

The invention discloses a preparation method and application of microfibrillated silk fiber aerogel. The preparation method comprises the following steps: by taking waste silk fibers processed and produced in factories as raw materials, carrying out chemical and mechanical pretreatment and silane coupling agent hydrophobization modification, and then preparing the aerogel material by utilizing a vacuum freeze-drying method. Silk fibers which are rich in resources and low in price are used as raw materials, the preparation cost can be remarkably reduced, the production process is simplified, the prepared microfibrillated silk fiber aerogel has the excellent performance of low cost, low density, high porosity, biodegradability and the like, various organic solvents and oil pollutants in sewage can be efficiently adsorbed, and the microfibrillated silk fiber aerogel has a good application prospect. The adsorbent is high in adsorption capacity, high in rate, good in mechanical property, capable of being repeatedly used, good in heat preservation and heat insulation performance and easy to degrade after being used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing microfibrillated silk fiber-based aerogel applied in the fields of adsorption and thermal insulation, belonging to the technical field of aerogel materials. Background Art

[0002] Aerogel is a lightweight material that is often used in fields such as adsorption and thermal insulation due to its high porosity, low density and ultra-high specific surface area. Currently, silicon-based and carbon-based aerogels on the market have defects such as high production cost, complex production process, small adsorption capacity and poor thermal insulation performance. In summary, the development of multifunctional materials with low price, simple preparation process, strong adsorption capacity and excellent thermal insulation performance is a hot topic for scientific researchers. Biomass materials have been widely used in scientific research because of their green, environmentally friendly, renewable raw materials, abundant sources and biodegradable characteristics. Among them, cellulose aerogel is a biomass-based aerogel with good adsorption and thermal insulation properties, but the cellulose extraction process is complicated and energy-intensive, which will cause pollution to the environment, and the relatively poor mechanical properties make it difficult to recycle.

[0003] Silk refers to natural fibers formed by the mucus secreted by silkworms. Its main components are fibroin and sericin. It has the characteristics of high strength, good elasticity, light weight, hydrophilicity and hygroscopicity. It is widely used in clothing, sensing, biomedicine, adsorption and other fields. The silk processing and production process will produce a large amount of waste short silk fibers, resulting in a waste of resources. Therefore, the present invention attempts to utilize waste and prepare a multifunctional microfibrillated silk fiber-based aerogel material with good adsorption performance and thermal insulation performance using waste silk fiber raw materials. Summary of the invention

[0004] The technical problem solved by the present invention is to realize the recycling of waste biomass resources and to prepare a functional microfibrillated silk fiber aerogel material with low cost, simple process, reusability, biodegradability, high adsorption performance, super hydrophobicity and low thermal conductivity.

[0005] In order to solve the above problems, the present invention provides a method for preparing microfibrillated silk fiber-based aerogel, wherein the recycled waste silk fibers are physically cut and crushed, chemically treated and mechanically ground to prepare a microfibrillated silk fiber suspension having a micro-nano-scale special-shaped structure on the surface, and the fiber suspension is super-hydrophobicized by a silane coupling agent to achieve hydrophobic functionalization, and then the aerogel material is prepared by low-temperature freezing and vacuum freeze-drying.

[0006] Specifically, the present invention also provides a specific preparation method of the above-mentioned microfibrillated silk fiber aerogel, comprising the following steps:

[0007] Step 1: Preparation of microfibrillated silk fiber suspension: Use a fiber cutter to mechanically treat silk fibers into powder to obtain silk staple fibers; then use a NaOH solution to perform surface degumming on the silk staple fibers to remove the sericin on the surface of the silk fibers until the silk fibroin inside the fibers is exposed, and use deionized water to rinse the silk staple fibers; then use a pulping machine to mechanically grind the silk staple fibers to obtain microfibrillated silk fibers with a large number of irregular micro-nano filamentous structures on the surface, and add deionized water and stir at room temperature to prepare a microfibrillated silk fiber suspension;

[0008] Step 2: hydrophobic modification of the microfibrillated silk fiber suspension: after adjusting the pH value of the microfibrillated silk fiber suspension obtained in step 1 to acidic, a silane coupling agent is added thereto, and the mixture is stirred and reacted at room temperature to obtain a hydrophobically modified microfibrillated silk fiber suspension;

[0009] Step 3: Preparation of microfibrillated silk fiber aerogel: The hydrophobically modified silk fiber suspension obtained in step 2 is placed in a mold for freeze molding, and freeze-dried using a vacuum freeze dryer to prepare microfibrillated silk fiber aerogel.

[0010] Preferably, the conditions of the mechanical grinding treatment in step 1 are: beating degree 20-70°SR, temperature 25±5°C, and time 0.5-3h.

[0011] Preferably, in step 1, a fiber cutter is used to mechanically treat the silk fibers, and the length distribution of the obtained silk staple fibers is about 200-20000 μm.

[0012] Preferably, the surface degumming treatment in step 1 is specifically as follows: placing the silk staple fibers in a NaOH solution, stirring at 90-150° C. for 1-3 hours, and washing the fibers with deionized water until they are neutral; the concentration of the NaOH solution used is 1.0-10.0 wt %.

[0013] Preferably, the content of microfibrillated silk fibers in the microfibrillated silk suspension prepared in step 1 is 0.1-3.0 wt %.

[0014] Preferably, in step 2, the pH value is adjusted to 3-5 using an acid, and the acid is hydrochloric acid, acetic acid, etc.

[0015] Preferably, in step 2, the silane coupling agent is methyltrimethoxysilane, epoxysilane coupling agent, vinyltrimethoxysilane, etc., and the concentration of the silane coupling agent is 0.1-7wt%.

[0016] Preferably, the stirring reaction conditions in step 2 are: rotation speed 800-1200 rpm, time 4-6 hours.

[0017] Preferably, the specific conditions for freeze molding in step 3 are: freezing in a refrigerator at -20 to -25°C for 7 to 36 hours, or freezing in liquid nitrogen at -196°C for 5 to 10 minutes.

[0018] Preferably, the freeze-drying conditions in step 3 are: temperature -60 to -70°C, time 24 to 72 hours.

[0019] The present invention also provides the use of the microfibrillated silk fiber aerogel material as an oil spill adsorption material or oil filtration and recovery material. The density of the aerogel is 2.0 to 12.0 mg / cm 3 The adsorption ratio is 164-240g / g, the contact angle is as high as 170°, and the thermal conductivity can be as low as 0.03W / (mK).

[0020] The present invention also provides the application of the above-mentioned microfibrillated silk fiber aerogel material in the fields of oil or organic solvent adsorption (oil-water separation and oil recovery) and thermal insulation.

[0021] Preferably, the application includes selectively adsorbing one or more of mineral oil, vegetable oil, vacuum pump oil, engine oil, soybean oil and organic solvents. The organic solvent includes any one or more of dimethyl sulfoxide, toluene, N,N-dimethylformamide, chloroform, ethanol, isopropanol and acetone.

[0022] The microfibrillated silk fiber aerogel obtained by the present invention has excellent properties such as low cost, low density, high porosity (up to 99.8%) and biodegradability. It can efficiently adsorb a variety of organic solvents and oil pollutants in sewage, has high adsorption capacity, fast rate, good mechanical properties and can be reused many times. It also has good thermal insulation properties and is easy to degrade after use.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention uses silk fibers discarded from factory processing and production to perform surface alkali treatment and mechanical treatment to prepare microfibrillated silk suspension, and uses silanization modification and vacuum freezing methods to achieve the preparation of aerogel materials. The present invention uses silk fibers, which are abundant in resources and low in price, as raw materials, which can significantly improve the material's formability, adsorption performance, and reusability, and reduce thermal conductivity, simplify the preparation process, and significantly reduce the preparation cost.

[0025] 2. The microfibrillated silk fiber aerogel material prepared by the present invention has stable formability and a three-dimensional porous structure, and its density is 4.8-18.0 mg / cm 3, can quickly absorb a variety of oils and organic solvents such as vegetable oil, vacuum pump oil, engine oil, chloroform, gasoline, white oil and toluene, with a liquid adsorption rate of up to 240g / g at room temperature; oil retention performance can be as high as 90%; excellent hydrophobic performance, contact angle reaches 150-170°;

[0026] 3. The microfibrillated silk fiber aerogel material prepared by the present invention can be used for oil recovery and repeated recycling by mechanical extrusion; the aerogel has excellent super hydrophobic and oleophilic properties, and can be used as a filter material, and can also be used for oil-water separation and oil spill recovery;

[0027] 4. The microfibrillated silk fiber aerogel material prepared by the present invention has a uniform and stable three-dimensional porous fiber entanglement structure. The aerogel has an ultra-low thermal conductivity coefficient and exhibits good thermal insulation properties. It can be used as a thermal insulation material in clothing, pipeline transportation, wall insulation and other fields, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of the internal structure of the aerogel prepared in Example 1.

[0029] Figure 2 The aerogel prepared in Example 1 selectively adsorbs chloroform in a mixture of water and chloroform; wherein, (a) is to clamp the aerogel with tweezers and insert it into water; (b) is to selectively adsorb chloroform without adsorbing water in a mixture of water and chloroform; (c) is to take out the aerogel after completely adsorbing chloroform in water.

[0030] Figure 3 This is a picture of the aerogel prepared in Example 1, which shows the aerogel adsorption-extrusion release-recycling of adsorbed oil;

[0031] Figure 4 The aerogel is placed on a hot plate with different temperatures, where (a) the bottom plate temperature is 150°C, (b) the bottom plate temperature is 100°C, and (c) the bottom plate temperature is 50°C. DETAILED DESCRIPTION

[0032] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0033] Example 1

[0034] This embodiment provides a method for preparing a microfibrillated silk fiber aerogel material, wherein the silk fibers are crushed and chemically and mechanically treated to obtain a uniform suspension of short silk fibers, the pH of the solution is adjusted to between 3 and 4, a silane coupling agent is added for hydrophobic modification, and the microfibrillated silk fiber aerogel is prepared by a vacuum freeze-drying method after freezing. The specific steps are as follows:

[0035] Step 1: Preparation of silk fiber suspension:

[0036] The silk fibers were mechanically crushed into fiber powders with a length of 1000-1500 μm. Then, they were placed in a 5 wt% NaOH solution and treated at 130°C for 1 h to remove the sericin on the surface of the silk fibers. Then, they were repeatedly rinsed with deionized water until the solution was neutral. Then, the silk fibers were mechanically ground with a beater (beating degree 20°SR, 25±5°C, 0.5 h) to obtain microfibrillated silk fibers with micro-nano scale shaped filamentous structures on the surface. Deionized water was added and stirred with a magnetic stirrer at room temperature for 2 h to prepare a fiber suspension (0.2 wt%).

[0037] Step 2: Hydrophobic modification of microfibrillated silk fibers:

[0038] The pH of the suspension obtained in step 1 is adjusted to between 3 and 4 using glacial acetic acid, 1 wt % of vinyltrimethoxysilane is added dropwise to the suspension using a pipette, and stirred for 6 h using a magnetic stirrer at room temperature at a rotation speed of 1200 rpm to obtain a modified suspension;

[0039] Step 3: Preparation of microfibrillated silk fiber aerogel:

[0040] The modified suspension in step 2 is poured into a mold and placed in a refrigerator, and then frozen at -25°C for 10 hours; then, a freeze dryer is used to freeze-dry at -68°C for 48 hours to obtain microfibrillated silk fiber aerogel.

[0041] The silk fiber aerogel prepared in this example has a size of 4 cm × 4 cm × 2 cm (see Figure 1 ), the interior of the aerogel exhibits a uniform multi-level three-dimensional porous structure, and the measured density is 3.2 mg / cm 3 , the contact angle is 170°, and it is placed in a mixed solution of water and chloroform (the volume ratio of water to chloroform is 40:1). The aerogel can quickly and selectively adsorb chloroform from the mixed solution within 10 seconds (see Figure 2), the adsorption rate is 240g / g. The aerogel is placed in a mixed solution of water and vegetable oil (the volume ratio of water to vegetable oil is 10:1). The aerogel can selectively absorb the vegetable oil from the mixed solution of water and vegetable oil, and the vegetable oil inside the aerogel can be directly squeezed out for recovery by external extrusion. After extrusion, the aerogel can still return to its original shape and be placed in a mixed solution of water and vegetable oil (the volume ratio of water to vegetable oil is 10:1) again to absorb the vegetable oil. The aerogel can still be reused by oil absorption-extrusion (see Figure 3 ), the test found that the oil recovery efficiency through this method is higher than 90%, and the oil absorption rate of the aerogel for vegetable oil decreased by about 20% after 10 repeated extrusions, showing good reusability.

[0042] Example 2

[0043] This embodiment provides a method for preparing a microfibrillated silk fiber aerogel material, wherein the silk fibers are crushed and chemically and mechanically treated to obtain a uniform suspension of short silk fibers, the pH of the solution is adjusted to between 3 and 4, a silane coupling agent is added for hydrophobic modification, and the microfibrillated silk fiber aerogel is prepared by a vacuum freeze-drying method after freezing. The specific steps are as follows:

[0044] Step 1: Preparation of microfibrillated silk fiber suspension:

[0045] The silk fibers were mechanically crushed into fiber powders with a length of 1200-2000 μm. The silk fibers were placed in a 10 wt% NaOH solution and treated at 110°C for 50 min to remove the sericin on the surface of the silk fibers, and then repeatedly rinsed with deionized water until the solution was neutral; the silk fibers were then mechanically treated with a pulping machine (50 beating degrees, 25±5°C, 1 h) to obtain microfibrillated silk fibers with micro-nano scale shaped filamentous structures on the surface, and deionized water was added and stirred with a magnetic stirrer at room temperature for 1 h to prepare a fiber suspension (1.0 wt%).

[0046] Step 2: Hydrophobic modification of microfibrillated silk solution:

[0047] The pH of the solution obtained in step 1 was adjusted to 4 using glacial acetic acid, 2 wt % of methyltrimethoxysilane was added dropwise to the suspension using a pipette, and stirred for 5 h using a magnetic stirrer at room temperature at a rotation speed of 1000 rpm to obtain a modified suspension;

[0048] Step 3: Preparation of microfibrillated silk fiber aerogel:

[0049] The modified suspension in step 2 is poured into a mold and placed in a refrigerator, and then frozen at -25°C for 10 hours; then, a freeze dryer is used to freeze-dry at -68°C for 48 hours to obtain microfibrillated silk fiber aerogel.

[0050] The silk fiber aerogel with a size of 5 cm×5 cm×3 cm prepared in this example has a density of 5.6 g / cm 3 , with a contact angle of 170°, and placed in a mixed solution of water and mineral oil (the volume ratio of water to mineral oil is 40:1). The mineral oil is collected from the oil-water mixture by adopting a continuous pump suction method. Specifically, the aerogel is placed at the head end of the tube of the suction pump and placed in the oil-water mixed solution, and the pump is turned on to continuously suck the oil, thereby selectively filtering and recovering the mineral oil in the mixed solution.

[0051] Example 3

[0052] This embodiment provides a method for preparing a microfibrillated silk fiber aerogel material, wherein the silk fibers are crushed and chemically and mechanically treated to obtain a uniform suspension of short silk fibers, the pH of the solution is adjusted to between 3 and 4, a silane coupling agent is added for hydrophobic modification, and the microfibrillated silk fiber aerogel is prepared by a vacuum freeze-drying method after freezing. The specific steps are as follows:

[0053] Step 1: Preparation of microfibrillated silk fiber suspension:

[0054] The silk fibers were mechanically crushed into fiber powders with a length of 1200-2000 μm. The silk fibers were placed in a 5wt% NaOH solution and treated at 120°C for 1h to remove the sericin on the surface of the silk fibers, and then repeatedly rinsed with deionized water until neutral; the silk fibers were then mechanically treated with a beater (beating degree 40°SR, 25±5°C, 2h) to obtain microfibrillated silk fibers with micro-nano scale shaped filamentous structures on the surface, and deionized water was added and stirred with a magnetic stirrer at room temperature for 2h to prepare a fiber suspension (0.5wt%).

[0055] Step 2: Hydrophobic modification of microfibrillated silk suspension:

[0056] The pH of the suspension prepared in step 1 is adjusted to between 3 and 4 using hydrochloric acid, 4 wt % of methyltrimethoxysilane is added dropwise to the suspension using a pipette, and stirred for 5 h using a magnetic stirrer at room temperature at a rotation speed of 1000 rpm to obtain a modified suspension;

[0057] Step 3: Preparation of microfibrillated silk aerogel:

[0058] The modified suspension in step 2 is poured into a mold and placed in a refrigerator, and then frozen at -25°C for 10 hours; then, a freeze dryer is used to freeze-dry at -68°C for 48 hours to obtain microfibrillated silk fiber aerogel.

[0059] The density of the microfibrillated silk fiber aerogel with a size of 5 cm×5 cm×2 cm prepared in this example is 5.2 mg / cm 3 , contact angle of 160°, thermal conductivity of 0.06W / (mK). The aerogel was placed on a hot plate at 150, 100, and 50°C, and the temperature of the top of the aerogel was found to be approximately 42, 37, and 30°C (see Figure 4 ), showing excellent thermal insulation performance.

[0060] The above description is only a preferred embodiment of the present invention and is not any formal or substantial limitation of the present invention. It should be pointed out that a person skilled in the art can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing microfibrillated silk fiber aerogel, characterized in that: The following steps are involved: Step 1: Preparation of microfibrillated silk fiber suspension: using a fiber cutting machine to mechanically treat the silk fibers into powder to obtain silk staple fibers; Then, the silk staple fibers are subjected to surface degumming treatment using a NaOH solution, and then the silk staple fibers are rinsed using deionized water; then, the silk staple fibers are subjected to mechanical grinding treatment using a pulping machine to obtain microfibrillated silk fibers, and then deionized water is added and stirred at room temperature to prepare a microfibrillated silk fiber suspension; Step 2: hydrophobic modification of the microfibrillated silk fiber suspension: after adjusting the pH value of the microfibrillated silk fiber suspension obtained in step 1 to acidic, a silane coupling agent is added thereto, and the mixture is stirred and reacted at room temperature to obtain a hydrophobically modified microfibrillated silk fiber suspension; Step 3: Preparation of microfibrillated silk fiber aerogel: The hydrophobically modified silk fiber suspension obtained in step 2 is freeze-formed and then freeze-dried to obtain microfibrillated silk fiber aerogel.

2. The preparation method according to claim 1, characterized in that: The conditions of the mechanical grinding treatment in step 1 are: beating degree 20-70°SR, temperature 25±5°C, and time 0.5-3h.

3. The preparation method according to claim 1, characterized in that: In the step 1, a fiber cutter is used to mechanically treat the silk fibers, and the length of the obtained silk staple fibers is 200-20000 μm.

4. The preparation method according to claim 1, characterized in that: The surface degumming treatment in step 1 is specifically as follows: placing the silk staple fibers in a NaOH solution, stirring at 90-150° C. for 1-3 hours, and washing the fibers with deionized water until they are neutral; the concentration of the NaOH solution used is 1.0-10.0 wt %.

5. The preparation method according to claim 1, characterized in that: The content of microfibrillated silk fibers in the microfibrillated silk suspension in step 1 is 0.1-3.0 wt%.

6. The preparation method according to claim 1, characterized in that: In step 2, the pH value is adjusted to 3-5 using an acid, wherein the acid is hydrochloric acid or acetic acid; and the stirring reaction conditions in step 2 are: a rotation speed of 800-1200 rpm and a time of 4-6 hours.

7. The preparation method according to claim 1, characterized in that: In step 2, the silane coupling agent is methyltrimethoxysilane, epoxysilane coupling agent or vinyltrimethoxysilane, and the concentration of the silane coupling agent is 0.1-7wt%.

8. The preparation method according to claim 1, characterized in that: The freeze-molding conditions in step 3 are: freezing in a refrigerator at -20 to -25°C for 7 to 36 hours, or freezing in liquid nitrogen at -196°C for 5 to 10 minutes; the freeze-drying conditions in step 3 are: temperature at -60 to -70°C, time for 24 to 72 hours.

9. The microfibrillated silk fiber aerogel material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the microfibrillated silk fiber aerogel material according to claim 9 as an oil spill adsorption material or an oil filtration and recovery material, or use of the microfibrillated silk fiber aerogel material in the field of oil or organic solvent adsorption and thermal insulation.